Memorandum re Shortage of Nurses - Labour Party (Great Britain). National Executive Committee ; Labour Party (Great Britain). Advisory Committee on Public Health ; Joint Research Dept. of the Trades Union Congress and the Labour Party; MacCallum, Maude
1924-07 1924 1920s 8 pages - 4 - (92) Government Department; i.e., that compensation should be given to any nurse earning a salary if through her work she contracts a disease that renders her less able to earn a living than before she entered hospital. At the present time, a young girl who enters a sanatorium is offered £30 a year or thereabouts. If she contracts tuberculosis, though no doubt she is given a certain amount of treatment, eventually she may be obliged to resign and depend entirely upon herself for her maintenance. The same thing applies to fever hospitals. Girls enter just at the age when they are most liable to infection, and when measles, mumps, scarlet fever, etc., are likely to leave after effects. We can give specific cases where nurses who have contracted diseases, due directly to their work, after being given perhaps up to a year's salary, are left to look after themselves as best they can, with impaired health, and this in spite of the fact that a probationer entering hospital is obliged to produce a medical certificate of good health, and more often than not, is examined by a medical man appointed by the hospital, before she finally signs her agreement. The Labour Party, and Trades Unions in particular, could very greatly help to do away with these evils if when contributing money to the various hospitals, they made it a condition that no nurse in the service of the said hospital should be prevented from joining, or intimidated, or influenced to resign from her craft union. When the Professional Union of Trained Nurses (the only trade union of nurses in England, Scotland and Wales) was formed, Sir Arthur Stanley, Treasurer of St. Thomas's Hospital sent round a circular in which he stated:- 292/842/1/14